MICAL-mediated oxidation of actin and its effects on cytoskeletal and cellular dynamics - Rajan, Sudeepa; Terman, Jonathan R.; Reisler, Emil (Frontiers in Cell and Developmental Biology, 2023)
Actin and its dynamic structural remodelings are involved in multiple cellular functions, including maintaining cell shape and integrity, cytokinesis, motility, navigation, and muscle contraction. Many actin-binding proteins regulate the cytoskeleton to facilitate these functions. Recently, actin's post-translational modifications (PTMs) and their importance to actin functions have gained increasing recognition. The MICAL family of proteins has emerged as important actin's regulatory oxidation-reduction (Redox) enzymes, influencing actin’s properties both in vitro and in vivo. MICALs specifically bind to actin filaments and selectively oxidize actin’s methionine residues 44 and 47, which perturbs filaments' structure and leads to their disassembly. This review provides an overview of the MICALs and the impact of MICALs-mediated oxidation on actin's properties, including its assembly and disassembly, effects on other actin-binding proteins, and on cells and tissue systems.